Chloramphenicol base chemistry. Part 11:1 chloramphenicol base-derived thiourea-catalyzed enantioselective Michael addition of malononitrile to α, β-unsaturated ketones. Issue 7 (15th July 2017) - Yan, Linjie; Wang, Haifeng; Xiong, Fangjun; Tao, Yuan; Wu, Yan; Chen, Fener
Graphical abstract: Abstract: The first chloramphenicol base-derived thiourea-catalyzed enantioselective Michael addition of malononitrile to α, β -unsaturated ketones is reported. The Michael adducts were obtained in good to excellent yields (up to 98% yield) and enantioselectivities (up to 94% ee ). This reaction has a broad substrate scope to various α, β -unsaturated ketones. With this in mind, this methodology was successfully applied to the synthesis of a chiral piperidone, an advanced building block for dihydropyridinone P2X7 receptor antagonists. Abstract : ( S )-2-(3-Oxo-1, 3-diphenyl propyl)malononitrile: C18 H14 N2 O [α]D 20  = −4.0 ( c 1.0, CH2 Cl2 ) Source of chirality: catalyst6a ; asymmetric Michael addition Absolute configuration: ( S ) Abstract : ( S )-2-(1-(4-Methylphenyl)-3-oxo-3-phenylpropyl)malononitrile: C19 H16 N2 O [α]D 20  = −1.3 ( c 1.0, CH2 Cl2 ) Source of chirality: catalyst6a ; asymmetric Michael addition Absolute configuration: ( S ) Abstract : ( S )-2-(1-(4-Methoxyphenyl)-3-oxo-3-phenylpropyl)malononitrile: C19 H16 N2 O2 [α]D 20  = −2.0 ( c 0.48, CH2 Cl2 ) Source of chirality: catalyst6a ; asymmetric Michael addition Absolute configuration: ( S ) Abstract : ( S )-2-(1-(3-Methoxyphenyl)-3-oxo-3-phenylpropyl)malononitrile: C19 H16 N2 O2 [α]D 20  = −3.1 ( c 0.37, CH2 Cl2 ) Source of chirality: catalyst6a ; asymmetric Michael addition Absolute configuration: ( S ) Abstract : ( S )-2-(1-(4-Fluorophenyl)-3-oxo-3-phenylpropyl)malononitrile: C18 H13 FN2 O [α]D 20  = −0.4 ( c 1.0, CH2 Cl2 ) Source of chirality: catalyst6a ; asymmetric Michael addition Absolute configuration: ( S ) Abstract : ( S )-2-(1-(2-Fluorophenyl)-3-oxo-3-phenylpropyl)malononitrile: C18 H13 FN2 O [α]D 20  = +20 ( c 0.24, CH2 Cl2 ) Source of chirality: catalyst6a ; asymmetric Michael addition Absolute configuration: ( S ) Abstract : ( S )-2-(1-(4-Chlorophenyl)-3-oxo-3-phenylpropyl)malononitrile: C18 H13 ClN2 O [α]D 20  = −3.4 ( c 0.5, CH2 Cl2 ) Source of chirality: catalyst6a ; asymmetric Michael addition Absolute configuration: ( S ) Abstract : ( S )-2-(1-(3-Chlorophenyl)-3-oxo-3-phenylpropyl)malononitrile: C18 H13 ClN2 O [α]D 20  = −0.5 ( c 0.3, CH2 Cl2 ) Source of chirality: catalyst6a ; asymmetric Michael addition Absolute configuration: ( S ) Abstract : ( S )-2-(1-(4-Bromophenyl)-3-oxo-3-phenylpropyl)malononitrile: C18 H13 BrN2 O [α]D 20  = −4.3 ( c 1.15, CH2 Cl2 ) Source of chirality: catalyst6a ; asymmetric Michael addition Absolute configuration: ( S ) Abstract : ( S )-2-(1-(3-Bromophenyl)-3-oxo-3-phenylpropyl)malononitrile: C18 H13 BrN2 O [α]D 20  = −0.25 ( c 1.2, CH2 Cl2 ) Source of chirality: catalyst6a ; asymmetric Michael addition Absolute configuration: ( S ) Abstract : ( S )-2-(1-(2-Bromophenyl)-3-oxo-3-phenylpropyl)malononitrile: C18 H13 BrN2 O [α]D 20  = +16 ( c 1.0, CH2 Cl2 ) Source of chirality: catalyst6a ; asymmetric Michael addition Absolute configuration: ( S ) Abstract : ( S )-2-(1-(4-Trifluoromethylphenyl)-3-oxo-3-phenylpropyl)malononitrile: C19 H13 F3 N2 O [α]D 20  = −2.5 ( c 0.8, CHCl3 ) Source of chirality: catalyst6a ; asymmetric Michael addition Absolute configuration: ( S ) Abstract : ( S )-2-(1-(3-Trifluoromethylphenyl)-3-oxo-3-phenylpropyl)malononitrile: C19 H13 F3 N2 O [α]D 20  = −0.4 ( c 0.32, CH2 Cl2 ) Source of chirality: catalyst6a ; asymmetric Michael addition Absolute configuration: ( S ) Abstract : ( S )-2-(1-(4- tert -Butylphenyl)-3-oxo-3-phenylpropyl)malononitrile: C22 H22 N2 O [α]D 20  = +37.5 ( c 0.8, CH2 Cl2 ) Source of chirality: catalyst6a ; asymmetric Michael addition Absolute configuration: ( S ) Abstract : ( S )-2-(1-(3, 4-Dichlorophenyl)-3-oxo-3-phenylpropyl) malononitrile: C18 H12 Cl2 N2 O [α]D 20  = +6.6 ( c 0.44, CH2 Cl2 ) Source of chirality: catalyst6a ; asymmetric Michael addition Absolute configuration: ( S ) Abstract : ( S )-2-(1-(Naphthalen-2-yl)-3-oxo-3-phenylpropyl)malononitrile: C22 H16 N2 O [α]D 20  = −9.0 ( c 0.8, CH2 Cl2 ) Source of chirality: catalyst6a ; asymmetric Michael addition Absolute configuration: ( S ) Abstract : ( S )-2-(1-(Thiophen-2-yl)-3-oxo-3-phenylpropyl)malononitrile: C16 H12 N2 OS [α]D 20  = +10 ( c 0.5, CH2 Cl2 ) Source of chirality: catalyst6a ; asymmetric Michael addition Absolute configuration: ( S ) Abstract : ( S )-2-(1-(Thiophen-2-yl)-3-oxo-3-phenylpropyl)malononitrile: C16 H11 ClN2 OS [α]D 20  = +17.6 ( c 0.37, CH2 Cl2 ) Source of chirality: catalyst6a ; asymmetric Michael addition Absolute configuration: ( S ) Abstract : ( R, E )-2-(5-Oxo-1, 5-diphenyl pent-1-en-3-yl)malononitrile: C20 H16 N2 O [α]D 20  = −5.65 ( c 0.23, CH2 Cl2 ) Source of chirality: catalyst6a ; asymmetric Michael addition Absolute configuration: ( S ) Abstract : ( S )-2-(1-Cyclohexyl-3-Oxo-3-phenylpropyl)malononitrile: C18 H20 N2 O [α]D 20  = +40.65 ( c 0.46, CH2 Cl2 ) Source of chirality: catalyst6a ; asymmetric Michael addition Absolute configuration: ( S ) Abstract : ( S )-3-(2, 2-Methyl-5-Oxo-5-phenylpentyl)malononitrile: C16 H18 N2 O [α]D 20  = +26.32 ( c 0.19, CH2 Cl2 ) Source of chirality: catalyst6a ; asymmetric Michael addition Absolute configuration: ( S ) Abstract : ( S )-2-(3-(4-Methoxyphenyl)-3-Oxo-1-phenylpropyl)malononitrile: C19 H16 N2 O2 [α]D 20  = +13.8 ( c 0.3, CH2 Cl2 ) Source of chirality: catalyst6a ; asymmetric Michael addition Absolute configuration: ( S ) Abstract : ( S )-2-(3-(4-Nitrophenyl)-3-Oxo-1-phenylpropyl)malononitrile: C18 H13 N3 O3 [α]D 20  = +16.8 ( c 0.31, CH2 Cl2 ) Source of chirality: catalyst6a ; asymmetric Michael addition Absolute configuration: ( S ) Abstract : ( S )-2-(3-(4-Chlorophenyl)-3-Oxo-1-phenylpropyl)malononitrile: C18 H13 ClN2 O [α]D 20  = +21.8 ( c 0.22, CH2 Cl2 ) Source of chirality: catalyst6a ; asymmetric Michael addition Absolute configuration: ( S ) Abstract : ( S )-2-(3-(2-Naphthyl)-3-Oxo-1-phenylpropyl)malononitrile: C22 H16 N2 O [α]D 20  = +41.7 ( c 0.22, CH2 Cl2 ) Source of chirality: catalyst6a ; asymmetric Michael addition Absolute configuration: ( S ) Abstract : ( S )-2-(3-(2-Thienyl)-3-Oxo-1-phenylpropyl)malononitrile: C16 H12 N2 OS [α]D 20  = +5.8 ( c 0.38, CH2 Cl2 ) Source of chirality: catalyst6a ; asymmetric Michael addition Absolute configuration: ( S ) Abstract : ( S )-3-(4-Fluorophenyl)-5-oxo-5-phenylpentanoic acid: C17 H15 FO3 [α]D 20  = +16 ( c 1.0, CH2 Cl2 ) Source of chirality: compound13e Absolute configuration: ( S ) Abstract : Benzyl ( S )-3-(4-fluorophenyl)-5-oxo-5-phenylpentanoate: C24 H21 FO3 [α]D 20  = +8.5 ( c 1.0, CH2 Cl2 ) Source of chirality: compound14 Absolute configuration: ( S ) Abstract : 1-Benzyl-5-phenyl ( R )-3-(4-fluorophenyl)pentanedioate: C24 H21 FO4 [α]D 20  = +20.5 ( c 1.0, CH2 Cl2 ) Source of chirality: compound15 Absolute configuration: ( S ) Abstract : ( R )-3-(4-Fluorophenyl)-5-oxo-5-phenoxypentanoic acid: C17 H15 FO4 [α]D 20  = −11.3 ( c 1.0, CHCl3 ) Source of chirality: compound16 Absolute configuration: ( S ) Abstract : ( R )-3-(4-Fluorophenyl)-5-methoxy-5-oxopentanoic acid: C12 H13 FO4 [α]D 20  = +8.5 ( c 1.0, CHCl3 ) Source of chirality: compound17 Absolute configuration: ( S ) Abstract : ( S )-4-(4-Fluorophenyl)-6-oxo-1, 4, 5, 6-tetrahydropyridine-3-carboxylic acid methyl ester: C13 H12 FNO3 [α]D 20  = +52.4 ( c 1.2, CHCl3 ) Source of chirality: compound18 Absolute configuration: ( S )